Obesity Among Female Lecturers During the Covid-19 Pandemic in Aceh, Indonesia: A Retrospective Study - Agus Hendra Al Rahmad; Alfridsyah Alfridsyah; Ichsan Ichsan; Rini Handayani (JURNAL INFO KESEHATAN, 2025)
The Covid-19 pandemic has led to changes in uncontrolled consumption patterns and decreased physical activity among female teaching staff members. Therefore, they tend to gain weight, leading to non-communicable diseases (NCDs) and comorbidities. In support of the government’s efforts, the prevalence of obesity must be reduced through healthy behavioral changes. This study aimed to identify the cause of obesity among female lecturers in Aceh during the Covid-19 pandemic. This study used a case-control design and was conducted in Aceh Province from March to June 2021. The sample consisted of 65 female lecturers (obese) and 65 controls (non-obese), obtained by purposive sampling. Physical activity, NCDs history, anthropometric, BMI, and blood pressure data were collected and analyzed using the chi-square test at a 95% confidence interval (CI). Results found that Female lecturers in Aceh had a higher prevalence of obesity (55.4%). This was because of age > 45 years (p= 0.013; AOR= 2.42), junk food consumption (p= 0.017; AOR= 2.33), not on a diet (p= 0.034; AOR= 2.13), and less physical activity (p= 0.012; AOR= 2.79). During the Covid-19 pandemic, neither income nor pickle consumption were risk factors for obesity (p > 0.05). However, arthritis (p= 0.034; AOR= 2.12) and hypertension (p= 0.003; AOR= 2.93) were present in a high proportion of obese female lecturers (p < 0.05). Additionally, the risk of obesity during the Covid-19 pandemic in Aceh was unrelated (p > 0.05) to diabetes, high cholesterol, and heart disease. In conclusion, obesity among female lecturers in Aceh was caused by risk factors such as age, junk food consumption, and lack of physical activity during the Covid-19 pandemic. It is also associated with NCDs including arthritis and hypertension. It is hoped that avoiding obesity will prevent the emergence of non-communicable diseases.